Tingkat Kepuasan Petani Terhadap Kinerja Penyuluh Pertanian dalam Mendukung Pertanian Berkelanjutan di Desa Timoreng Panua, Kabupaten Sidrap - Zul Fadli; Aksal Mursalat; Ayu Wulandary (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2025)
The condition of agricultural productivity in Kecamatan Panca Rijang shows fluctuations from time to time. It is important to know the extent to which farmers are satisfied with the performance of agricultural extension workers, considering that the role of extension workers has a direct relationship with agricultural production, especially in the research area. This study aims to analyze the level of farmer satisfaction with the performance of agricultural extension workers in supporting sustainable agricultural practices in Timoreng Panua Village. The population in this study amounted to 629 farmers, with a sample size of 42 respondents selected through specific techniques. Data was collected by distributing questionnaires to farmers living in Timoreng Panua Village. The data obtained were then analyzed quantitatively using the Importance Performance Analysis (IPA) method. The results showed that the level of farmer satisfaction with the performance of agricultural extension workers was in the very satisfied category, with an IPA score of 92.55%. The five performance attributes must be maintained based on the IPA Cartesian diagram. They contribute significantly to farmer satisfaction: participation, social interaction, community development, increased farmer income, and production efficiency. These five attributes are important indicators in assessing the effectiveness of extension workers' performance in the field and as benchmarks in developing sustainable agriculture programs in the future.